Pengaruh Latihan Kelenturan Pinggang Terhadap Keterampilan Smash Dalam Permainan Bola Voli Ekstrakurikuler Sma Negeri 2 Kaur - Afrian, Afrian; Asnawati, Asnawati; Syaputra, Roni (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the effect of waist flexibility training on smash skills in the extracurricular volleyball game of SMAN 2 Kaur. This type of research is experimental research. This research sample is all extracurricular volleyball players SMAN 2 kaur which amounted to 18 people. It can be seen the improvement of volleyball smash skills through the initial test and final test. The initial test (pre test) the highest value was 15 and the value was 8, an average of 10.56. The final test (post test) the highest score was 18, the lowest score was 9, the average was 12.44. The initial test of 10.56 increased to the final test of 12.44. The instrument used in this study is volleyball smash skills Based on the pre-test and post-test data on the smash skills of the extracurricular volleyball game SMAN 2 Kaur, the results of the normality test were obtained, all of which were normally distributed data. Furthermore, the t test results show tcount: 4.95 > t table: 2,110. So this value indicates that waist flexibility training has a significant effect on improving smash skills. Thus the hypothesis that there is an effect of waist flexibility training on smash skills in volleyball games on players at SMAN 2 Kaur” is accepted.